Analysis on Cu-WC-Si as electrode for advancement in electro-discharge machining. (1st January 2013) - Abdul-Rani, Ahmad Majdi; Mahamat, Al Tidjani Zakaria
Selection of electrode material with high wear resistance is an important task prior to conducting electro-discharge machining (EDM). Although Copper-Tungsten electrode have high wear resistance, it is difficult to manufacture due to its variation of melting point and zero miscibility of copper (Cu) with Tungsten (W). This paper analyses the potential of Cu reinforced with tungsten carbide (WC) and silicon (Si) additive (Cu-WC-Si) as electrode material to reduce electrode wear due to erosion of copper. Cu-WC-Si was synthesised using high-energy dry ball milling with parameters such as milling time and the weight percentage of tungsten carbide and silicon as variables. Performance of Cu-WC-Si as EDM electrode was tested on machining of hardened tool steel. The result shows that the materials removal rate (MRR) increases with milling time but decreases with an increase in silicon content. Milling time also has an effect on electrode wear and surface roughness. The new Cu-WC-Si electrode material provides improvement in EDM with reduced electrode wear and good surface finish in comparison to Cu-W electrode.